Condilomas acuminados extragenital - Passos, Mauro R.L.; Frias, Márcia C.A.A.; Pinheiro, Vandira M.S.; Oliveira, Ledy H.S.; Cavalcanti, Sílvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
Twocases of extragenital condiloma acuminatum. both on abdominal surgery scars. are described. The firsl patient was a female who had a same-sex sexual relationship. Besides the condiloma acuminatum on an abdominal surgery scars she had vulvar HPV lesions and CINI. The second patient was a male which had no genital HPV lesions. Both patients reported having just one sexual partner. Both partners had had genital verrucous lesions. The possible reasons for these scars infeclions are discussed.